Study of Reaction Kinetics and Identification of Clotrimazole Degradation Compounds in Anti-Fungal Cream Preparations - Cellia Christiana Batubara; Ani Iryani; Linda Jati Kusumawardani (Helium: Journal of Science and Applied Chemistry, 2021)
Fungal infections of the skin can be treated with antifungal compounds, one of which is clotrimazole. Under certain conditions, clotrimazole can be degraded to imidazole and (o-chlorophenyl) diphenyl methanol which can cause skin irritation. This is because the storage conditions of the drug product during or after use if it is not suitable, can interfere with the stability of the drug product. Therefore, this study was conducted to obtain information regarding changes in clotrimazole levels, reaction order, reaction constant value, half-life, activation energy, and the possibility of compounds formed after the clotrimazole degradation process to determine the good storage conditions of the product. Clotrimazole levels were tested in the open and closed state of the packaging every day at different storage temperatures for three months. Changes in clotrimazole levels were measured using HPLC every week. In addition, the identification of compounds resulting from degradation was also tested using HPLC every month and continued using LC-MS/MS in the last week. The results of the analysis of clotrimazole levels, there was a decrease in levels but still in accordance with the specifications required by the Indonesian Pharmacopoeia. The greatest decrease in levels occurred in samples stored at a temperature of 40±2oC which reached 9133%. The decrease in clotrimazole levels followed a first-order reaction with the shortest half-life of 90 weeks and activation energy of 18.9 kJ/mol. Identification of the degraded compounds using HPLC and LC-MS/MS found imidazole compounds and (o-chlorophenyl) diphenyl methanol in samples stored at 25±2oC and 40±2oC. These compounds can cause skin irritation, but these compounds may not have a serious impact because they have a fairly large body threshold value of 220 mg/kg. This shows that clotrimazole cream stored at various temperatures, both at 5±2oC, 25±2oC, and 40±2oC can still be used for three months after the packaging is opened according to the in-use shelf life.